Soviet oil exports : trade adjustments, refining constraints, and market behavior - Chadwick, Margaret; Long, David; Nissanke, Machiko; Oxford Institute for Energy Studies (Oxford [Oxfordshire] ; New York : Published by Oxford University Press for the Oxford Institute for Energy Studies, 1987)
The book examines the oil export policies of the Soviet Union in the context of the Soviet balance of payments
Include bibliography
kjo 14/01/2019
Loans
Keywords: Long David; Petroleum industry and trade; Soviet Union